Geobiology Microbial Mats in Sandy Deposits from the Archean Era to Today - Noffke, Nora.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book describes microbially induced sedimentary structures as new group in the Classification of Primary Sedimentary Structures. Those structures rise from the interaction of benthic microorganisms with physical sediment dynamics caused by waves and currents. We can observe the formation of those features today in modern coastal settings, where the structures are much more common than stromatolites. However, fossil structures occur since the earliest Archean, and are abundant throughout Earth history. The structures constitute a significant archive for the understanding of Earth$1 (Bs earliest worlds, and are important biosignatures for the detection of life on other planets. This book is for sedimentologists, paleontologists, microbiologists, and geobiologists likewise.s
Introduction -- Cyanobacteria: Taxonomic groups, physiology, photosynthesis, significance for Earth history -- Biofilms and Microbial Mats -- Microbial Interactions with Physical Sediment Dynamics in Modern Tidal Settings -- Microbially Induced sedimentary Structures -- Distribution of Microbially Induced Sedimentary Structures in the Fossil Record -- Field Trip Sites: Modern and Ancient -- Significance of Structures as Biosignatures for the Detection of Life on other Planets.
Keywords: Geography; Life sciences; Sedimentology; Microbiology; Astrobiology; Earth Sciences; Sedimentology; Astrobiology; Microbiology; Biogeosciences